2017
DOI: 10.1128/aac.02474-16
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of CTX-M-2, CTX-M-55, CMY-2, FosA3, and QnrB19 in Extraintestinal Pathogenic Escherichia coli from Poultry in Brazil

Abstract: E xtraintestinal pathogenic Escherichia coli (ExPEC) is a pathogen that causes a wide range of diseases worldwide (1). Based on molecular and phenotypic analysis, many reports suggest that poultry is a reservoir of ExPEC (1, 2). In addition to having pathogenic potential, many ExPEC lineages are multidrug resistant, leaving treatment options scarce (1). In this study, we report the coexistence of plasmid-mediated resistance to cephalosporins, quinolones, and fosfomycin in virulent lineages of ExPEC from poultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…There is few data about PMQR determinants either in humans or in animals in Brazil, therefore the prevalence of these genes is poorly understood. Another study in Brazil, also reported the gene qnrB19 carried by ColElike plasmids in four ExPEC isolates from poultry (Cunha et al, 2017).…”
Section: Resultsmentioning
confidence: 87%
“…There is few data about PMQR determinants either in humans or in animals in Brazil, therefore the prevalence of these genes is poorly understood. Another study in Brazil, also reported the gene qnrB19 carried by ColElike plasmids in four ExPEC isolates from poultry (Cunha et al, 2017).…”
Section: Resultsmentioning
confidence: 87%
“…Part of isolates characterized by Fernandes and coworkers was not able to transfer bla CTX-M-2 to E. coli, suggesting a possible chromosomal location of this gene [145]. In contrast, in E. coli, most studies suggest a chromosomal location of bla CTX-M-2 with a few reports of this gene in plasmids belonging to IncK, IncHI2, IncP incompatibility groups ranging from 35 to 280 kb [137,139,146,147,157]. Always when investigated, both in Salmonella sp.…”
Section: Streptococcus Sppmentioning
confidence: 96%
“…Studies indicate that these genes are mainly carried by E. coli and nontyphoid Salmonella, but also by Escherichia fergusonii, Klebsiella pneumoniae, Citrobacter diversus, and Proteus mirabilis [136][137][138][139][140]. Reports include animals on farms [36,[136][137][138][141][142][143][144][145][146][147], whole carcasses, or meat pieces available in Brazilian retail markets [69,136,138,140,145,148,149], and exported chicken meat [150][151][152]. The same genes were detected in turkeys with clinical signs of colibacillosis [153].…”
Section: Streptococcus Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…UTIs would be found to harbor fosA3-mediating plasmids in high frequency in China 145) . Moreover, FosA3 producers have also been spreading outside of Asia [146][147][148][149][150] . Therefore, further prevalence of fosA3 among the ESBL-producing E. coli showing resistance to fluoroquinolones, which are mostly E. coli ST131 subclones, H30 151,152) and H30Rx 153) clades, should be more carefully monitored in days to come within the community, especially in UTI patients 154) .…”
Section: Tenri Japanmentioning
confidence: 99%